Total Phenolics and Antioxidant Activity of Horsemint (Mentha Longifolia) - NAWAZ BHATTI, HAQ; JABBAR, ABDUL; Ul-Arifeen, Wasim- (Asian Journal of Chemistry, 2010)
Phytochemicals are receiving a great interest due to their unique antioxidant property. Plants are the rich source of phytochemicals which are important from antioxidant point of view. Due to their natural source, these antioxidants are thought to be safer. The present research work was designed to investigate the antioxidant activity of Mentha longifolia (horsemint). Horsemint showed the total phenolic contents range from 2.95 ± 07-5.16 ± 0.15 gallic acid equivalent (GAE) g/100 g, total flavonoids, 2.00 ± 0.06-14.94 ± 0.35 CE g/100 g, percentage inhibition of peroxidation was (93.1 ± 1.11-97 ± 1.64 % and low IC50 values (12.46 ± 0.37- 22.09 ± 0.66 μg/mL) for DPPH free radial scavenging. The antioxidant activity of horsemint extracts showed significant (p < 0.05) differences with in different solvent concentration. From the results it can be concluded that horsemint could be an efficient source of antioxidants.